Study of the role of hysteroscopy with dilation and curettage in post- menopausal bleeding: a cross sectional study - Padmawar, Atul; Khande, Ankita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Abnormal uterine bleeding is defined as any type of bleeding in which the duration, frequency or amount is excessive for an individual patient. Hysteroscopy has ushered a new era in the evaluation of abnormal uterine bleeding. With this background, we conducted a study to find the role of hysteroscopy with dilation and curettage in post-menopausal bleeding. Methods: It was an observational study conducted in the department of obstetrics and gynecology of a tertiary care hospital in Maharashtra. Post-menopausal patients with abnormal uterine bleeding, admitted in the period of March 2018 to September 2019 were included in the study. A pretested and predesigned questionnaire was used to collect the data. Hysteroscopy with dilation and curettage was done and samples were sent for histopathology. Results: Bleeding was present in all the 30 cases. About 33.33% had pain abdomen, 56.67% had hot flushes, 10.00% had mass and 10% had other symptoms in the present study. The sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of hysteroscopy in diagnosing malignancy was 75%, 96.15%, 75%, 96.15% and 93.33% respectively. Conclusions: To conclude the most common cause of abnormal uterine bleeding in post-menopausal women in our study was polyp. The sensitivity and specificity of the hysteroscopy in diagnosing the malignant lesions is 75% and 96.15% respectively which corroborated with other study findings. Hysteroscopy with dilation and curettage is better alternative to hysterectomy and biopsy in most of the cases.